Bowel Preparation for Colonoscopy in Children: 1 Day PEG-3350 with Bisacodyl versus 3 Day Sennosides - ERTEM ŞAHİNOĞLU, DENİZ; TUTAR, ENGİN (KARGER, 2019)
Background and Objectives: Bowel preparation (BP) for colonoscopy is a challenging procedure in children and different regimens have been used for this purpose. Polyethylene glycol (PEG) is the most preferred agent in recent years. The primary aim of this study was to evaluate the efficacy of 1-day PEG-3350 with bisacodyl (PEG-B) and comparing it with 3-day sennosides A+B. Method: In this prospective, randomized, and single-blinded study, children aged 2-18 years were included in the PEG-B group for 1 day or in Senna group for 3 days. The effectiveness of BP was assessed according to the Ottawa and Boston BP scales, compliance and adverse effects were also recorded. Pre- and post-preparation biochemistry were obtained for investigation of safety of both regimens. Results: Successful BP was observed in 88.3% (n = 53/60) of PEG-B and 86% (n = 55/64) of Senna groups according to Boston scale, and it was 85% (n = 51/60) and 84.4% (n = 54/64), respectively, according to Ottawa scale. The cecal intubation rate was 96.7% (n = 58/60) in the PEG-B group and 93.8% (n = 60/64) in the Senna group. Ease of administration and disturbance in regular daily activities was better in the PEG-B group (p < 0.05). There was no major adverse event and biochemical abnormality in both groups. The correlation between Ottawa and Boston scales was found to be excellent (r(2) = -0.954, p < 0.01). Conclusions: The efficacy, safety, and adverse effect profile of 1-day BP with PEG-B regimen was found to be similar to 3-day sennosides regimen, however, the PEG-B regimen had advantages such as short duration, ease of administration, and better patient comfort. Also, high correlation rate between the Boston and Ottawa scales in pediatric patients was remarkable. (c) 2019 S. Karger AG, Basel
Keywords: Children; Colonoscopy; Bowel preparation; Polyethylene glycol 3350; Bisacodyl; Sennosides; POLYETHYLENE-GLYCOL 3350; HIGH-DOSE SENNA; EFFECTIVE REGIMEN; SODIUM-PHOSPHATE; EFFICACY; SAFETY; PEG; ELECTROLYTES; PROTOCOL; SCALE